Kedai Buku Orang Muda / Muhammad Zulhusni Hamzah - Hamzah, Muhammad Zulhusni (2021)
Kedai Buku Orang Muda or KBOM was established on April 3, 2021. The main objective of this business is to cultivate the practice of reading among the community in our country. The main product sold is definitely a book. The book produced is very beneficial in addition to its very affordable price. As for social media, the use of the Facebook application has been activated on June 10, 2021. Until today, the KBOM Book Facebook pages have been followed by a total of 169 Facebook social media users. For now, we have made a post by putting the book along with the price, giving a little synopsis of the related book and also posting posters of the writing to captivate the soul of the reader.